Pattern of self-reported adverse events related to COVID-19 vaccines in Saudi Arabia: A nationwide study - Alkhalifah, Joud Mohammed; Al Seraihi, Ahad; Al-Tawfiq, Jaffar A.; Alshehri, Badr Fadhel; Alhaluli, Alhanouf Hani; Alsulais, Naif Mansour; Alessa, Mohammed Mesfer; Seddiq, Waleed; Aljeri, Thamer; Qahtani, Mohammad Hassan; Barry, Mazin; Al-Otaiby, Maram (Frontiers in Public Health, 2023)
Background: Vaccination against coronavirus disease 2019 (COVID-19) is the most effective way to end the pandemic. Any development of adverse events (AEs) from various vaccines should be reported. We therefore aimed to explore major and minor AEs among vaccinated individuals in Saudi Arabia. Methods: This is a nationwide report based on the Saudi Arabian Ministry of Health (MOH) registry. It included those who received COVID-19 vaccines from 17th December 2020 to 31st December 2021. The study included spontaneous self-reported adverse effects to COVID-19 vaccines where the study participants used a governmental mobile app (Sehhaty) to report their AEs following vaccination using a checklist option that included a selection of side-effects. The primary outcome was to determine AEs reported within 14 days of vaccination which included injection site itching, pain, reaction, redness, swelling, anxiety, dizziness, fever, headache, hoarseness, itchiness, loss of consciousness, nausea, heartburn, sleep disruption, fatigue, seizures, anaphylaxis, shortness of breath, wheezing, swelling of lips, face, and throat, loss of consciousness, and admissions into the intensive care unit (ICU). Results: The study included a total number of 28,031 individuals who reported 74,142 adverse events (AEs); which were further classified into minor and major adverse events including ICU admissions post vaccination. Of the reported AEs, 38,309 (53.6%) side-effects were reported following Pfizer-BioNTech, 32,223 (45%) following Oxford-AstraZeneca, and 948 (1.3%) following Moderna. The following reported AEs were statistically significant between the different vaccine types: shortness of breathof breathing, dizziness, fever above 39°C, headache, hoarseness, injection site reactions, itchiness, nausea, sleep disruption, fatigue, wheezing, swelling of lips/face andthroat, and loss of consciousness (p-value < 0.05). Fever and seizure were the only statistically significant AEs amongst the number of vaccine doses received (p-value < 0.05). Ten ICU admissions were reported in the 14 days observation period post-COVID-19 vaccination. Conclusion: This study demonstrated that the most prevalent SARS-CoV-2 vaccine side-effects among adults in Saudi Arabia were mild in nature. This information will help reduce vaccine hesitancy and encourage further mass vaccination to combat the COVID-19 pandemic, especially as booster doses are now available.